Activities of Daily Living and Outcomes in Heart Failure - Dunlay, Shannon M.; Manemann, Sheila M.; Chamberlain, Alanna M.; Cheville, Andrea L.; Jiang, Ruoxiang; Weston, Susan A.; Roger, Véronique L. (Circulation. Heart failure, 2015)
Chronic disease can contribute to functional disability, which can degrade quality of life. However, the prevalence of functional disability and its association with outcomes among patients with heart failure requires further study. Southeastern Minnesota residents with heart failure were enrolled from September 2003 through January 2012 into a cohort study with follow-up through December 2012. Difficulty with 9 activities of daily living (ADLs) was assessed by a questionnaire. Patients were divided into 3 categories of ADL difficulty (no/minimal, moderate, severe). The associations of ADL difficulty with mortality and hospitalization were assessed using Cox and Andersen-Gill models. Among 1128 patients (mean age, 74.7 years; 49.2% female), a majority (59.4%) reported difficulty with one or more ADLs at enrollment, with 272 (24.1%) and 146 (12.9%) experiencing moderate and severe difficulty, respectively. After a mean (SD) follow-up of 3.2 (2.4) years, 614 patients (54.4%) had died. Mortality increased with increasing ADL difficulty; the hazard ratio (95% confidence interval) for death was 1.49 (1.22-1.82) and 2.26 (1.79-2.86) for those with moderate and severe difficulty, respectively, compared to those with no/minimal difficulty (Ptrend<0.001). Patients with moderate and severe difficulty were at an increased risk for all-cause and noncardiovascular hospitalization. In a second assessment, 17.7% of survivors reported more difficulty with ADLs and patients with persistently severe or worsening difficulty were at an increased risk for death (hazard ratio, 2.10; 95% confidence interval, 1.71-2.58; P<0.001) and hospitalization (hazard ratio, 1.51; 95% confidence interval, 1.31-1.74; P<0.001). Functional disability is common in patients with heart failure, can progress over time, and is associated with adverse prognosis.